Innovation in Disaster Mitigation Communication Model, Coordination, and Digital Literacy after the Cianjur Earthquake Disaster - Edy Prihantoro; Ainun Rahma Yusufina; Noviawan Rasyid Ohorella (Ikatan Sarjana Komunikasi Indonesia, 2024)
Indonesia is vulnerable to natural disasters, including earthquake. Earthquake has an impact on the community including environmental, property, and psychological damage as well as loss of life. Such an impact also happened to earthquake-stricken Cianjur in West Java, which required disaster mitigation and digital literacy to deal with it. The aim of this research is to determine innovations in disaster mitigation communication models, coordination and digital literacy after the Cianjur earthquake. This is a form of handling the impact of a natural disaster before and after it occurs. The theory used in this research is Haddow Disaster Communication focusing on customer focus, leadership commitment, situational awareness, and media partnership. The method used in this research is descriptive qualitative conducted by collecting data through field observations, in-depth interviews and focus group discussions. The results of this research are innovations in disaster mitigation communication models to become disaster mitigation models in Cianjur in the future, know the coordination paths between the parties and the community in case of a disaster, and provide digital literacy for the people of Cianjur through emergency response call centers and WA groups to disseminate information to the public. The efforts of the parties involved in disaster mitigation aim to help the community reduce the risk of disaster affecting physical development, increase the ability of the community in disaster risk mitigation and get an understanding of the community’s access to disaster information.